INOVASI JATHILAN PRODI SENDRARIYA SEBAGAI UPAYA MEMPERTAHANKAN KEEKSISANNYA DI YOGYAKARTA - Asep Saepudin; Subuh Subuh; Sabatinus Prakasa (Pendidikan Seni Drama Tari dan Musik, Universitas Sultan Ageng Tirtayasa, 2021)
Abstract : The purpose of this research is to find out the various innovations made by Sendrariya Prodi Group in maintaining its existence in the Jathilan lovers community. A descriptive method of analysis is used in this research which is to explain the existing data followed by analysis. The research phase includes data collection, classification, and analysis. Data collection is conducted through observation, interviews, and documents, while data analysis is conducted in the research laboratory after all data is collected. Prodi Sendrariya is one of the lumping horse art communities or communities that is currently popular among actors and connoisseurs of Art in Yogyakarta. Prodi Sendrariya was established on December 24, 2017. This group chose to innovate in its art to stand out from other communities in Yogyakarta. Sendrariya is one of the groups that follow the development of the market by preparing what the public wants through its various innovations. The results of the research were obtained that Prodi Sendrariya has made various innovations to keep the group exists in the community, among others in the pattern of performances (including governance, costumes, performance packaging, working on other genres outside Jathilan) as well as incorporating jaipong drum instruments into the group in various performances. Kendang jaipong functioned to accompany Balinese, Banyuwangi, Banyumas, Javanese, and Sundanese style performances.